(untitled) - Chang, Raymond (Boston, MA., 2003)
the book includes all the core topics that are necessary for a solid foundation in general chemistry without sacrificing depth, clarity, or rigor. The third edition features new Spartan molecular models, animations correlated to the text, the addition of molecular orbital theory and more. General Chemistry: The Essential Concepts is 200 to 300 pages shorter than traditional two-semester textbooks and is much less expensive
Anh Văn chuyên ngành Sư phạm Hóa
Keywords: Chemistry